Analysis and design of a nonlinear stiffness and damping system with a scissor-like structure. (January 2016) - Sun, Xiuting; Jing, Xingjian
Abstract: An n -layer Scissor-Like Structured (SLS) vibration isolation platform is studied in this paper, focusing on the analysis and design of nonlinear stiffness, friction forces and damping characteristics for an advantageous vibration isolation performance. The system nonlinear stiffness and damping characteristics are theoretically investigated by considering the influence incurred by different structural parameters, friction forces and link inertia. Since stiffness and damping properties are both asymmetrical nonlinear functions, and Coulomb friction is piecewise nonlinear function, Perturbation Method (PM) and Average Method (AM) are applied together to achieve better solutions. The vibration isolation performance of the SLS platform is compared with known quasi-zero-stiffness vibration isolators in the literature, and a typical application case study as a vehicle seat suspension is also conducted, subjected to different load masses, and base excitations. The results show that much better vibration isolation performance and loading capacity can be easily achieved with the SLS platform by designing structural parameters, and the scissor-like structure provides a very powerful, practical and passive solution to design and realization of beneficial nonlinear stiffness and damping characteristics in vibration control.